Psychometric characteristics of the ECR-R (Experiences in Close Relationships-Revised) in Ecuadorian population. - Díaz Mosquera, Elena; Latorre Vaca, Grace; Merlyn Sacoto, Marie-France; Moreta Herrera, Rodrigo; Nóblega, Magaly (Instituto de Investigaciones Psicológicas, 2022)
The aim of the present study was to analyze the psychometric characteristics of the Experiences in Close Relationships-Revised (ECR-R) scale in young Ecuadorian adults. The participants were 641 university students from 20 to 25 years old, from two institutions in the city of Quito, to whom the test was applied. Using the Confirmatory Factor Analysis technique, it was verified that the results found were in accordance with the Peruvian ECR-R model. Therefore, the Ecuadorian version was made up of the 27 items of the Peruvian version, which correspond to the two original dimensions of the scale: Anxiety and Avoidance, the latter dimension consisting of two factors, one of direct items and the other of inverse items. An adequate reliability of the factors of Anxiety (α = .91; ω = .91), Inverse avoidance (α = .90; ω = .89) and Direct avoidance (α = .72; ω = .83) was found.